Frequency of Celiac Disease in Adult Patients with Typical or Atypical Malabsorption Symptoms in Isfahan, Iran - Mohammad Hassan Emami; Soheila Kouhestani; Somayeh Karimi; Abdolmahdi Baghaei; Mohsen Janghorbani; Nahid Jamali; Ali Gholamrezaei (Gastroenterology Research and Practice)
Aim. Atypical presentations of celiac disease (CD) have now been shown to be much more common than classical (typical) form. We evaluated the frequency of CD among adult patients with typical or atypical symptoms of CD. Materials and Methods. Patients referred to two outpatient gastroenterology clinics in Isfahan (IRAN) were categorized into those with typical or atypical symptoms of CD. IgA antitissue transglutaminase antibody was assessed and followed by duodenal biopsy. In patients for whom endoscopy was indicated (independent of the serology), duodenal biopsy was taken. Histopathological changes were assessed according to the Marsh classification. Results. During the study period, 151 and 173 patients with typical and atypical symptoms were evaluated (mean age = 32.8±12.6 and 35.8±14.8 years, 47.0% and 56.0% female, resp.). Frequency of CD in patients with typical and atypical symptoms was calculated, respectively, as 5.9% (9/151) and 1.25% (3/173) based on positive serology and pathology. The overall frequency was estimated as at least 9.2% (14/151) and 4.0% (7/173) when data of seronegative patients were also considered. Conclusions. CD is more frequent among patients with typical symptoms of malabsorption and these patients should undergo duodenal biopsy, irrespective of the serology. In patients with atypical symptoms, serological tests should be performed followed by endoscopic biopsy, and routine duodenal biopsy is recommended when endoscopic evaluation is indicated because of symptoms.